2010
DOI: 10.1121/1.3385171
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cognitive load and frustration on drivers’ speech.

Abstract: Secondary tasks such as cell phone calls or interaction with automated speech dialog systems (SDSs) increase the driver’s cognitive load as well as the probability of driving errors. This study analyzes speech production variations due to cognitive load and emotional state of drivers in real driving conditions. Speech samples were acquired from 24 female and 17 male subjects (approximately 8.5 h of data) while talking to a co-driver and communicating with two automated call centers, with emotional states (neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Past literature on emotions and stress suggests that a number of speech production parameters can be affected by varying speech modalities [18][19][20][21]. In this section, we extract a set of speech parameters derived from the linear model of speech production and evaluate their correlation with the perceptual excitement level in the commentators audio.…”
Section: Excitement Measurement In Speechmentioning
confidence: 99%
See 2 more Smart Citations
“…Past literature on emotions and stress suggests that a number of speech production parameters can be affected by varying speech modalities [18][19][20][21]. In this section, we extract a set of speech parameters derived from the linear model of speech production and evaluate their correlation with the perceptual excitement level in the commentators audio.…”
Section: Excitement Measurement In Speechmentioning
confidence: 99%
“…We have observed that SES, when combined with SCG, constitutes a more noise-robust spectral descriptor for emotion and stress classification than spectral slope [20]. The distribution of game-specific means of F 0 , F 1 , F 2 , and SCG across the four perceptual excitement levels is summarized in Figures 2, 3 degree of correlation between the speech parameters and perceived excitement levels, a linear regression was conducted.…”
Section: Excitement Measurement In Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…Boril et al [36] measured speech production variations during the interactions of drivers with commercial automated dialogue systems. They discussed that cognitive load and emotional states affect the number of query repetitions required for the users to obtain the information they are looking for.…”
Section: Introductionmentioning
confidence: 99%
“…As an important link in the human-computer interaction system, this method has received increasing attention in recent years. Speech emotion recognition has been widely applied to medical diagnosis [1], drowsy driving detection [2], and emotional state monitoring of students during the e-learning process [3].…”
Section: Introductionmentioning
confidence: 99%